Corn Silage Cost-Return Budget in Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R. (My University, 2012)
This publication contains information for a projected budged reflecting expected income and cost based on typical corn silage production practices in the northeast region of Kansas.
MF2364_2012_12
Keywords: MF2364; Economics; Crops; MF